Synthesis, characterization and plant growth assessment of hybrid calcium oxide nanoparticles - A.S. BALAGANESH; B. CHANDAR SHEKAR (International Journal of Pharma and Bio Sciences, 2017)
Nanoscale materials exhibit novel chemical, physical and biological properties which are different from their bulk form. In the present study we have investigated synthesis and characterization of hybrid chitosan-calcium oxide nanoparticles for plant growth development in lab scale level. From the X-ray diffraction analysis the prepared nanoparticles shows polycrystalline nature with particles size varies between 1.97nm and 8.94 nm. Scanning electron microscopy revealed agglomeration of hybrid chitosan-calcium oxide nanoparticles. Energy dispersive X-ray spectroscopy analysis indicates that the prepared sample is composed of Ca, O and N elements. The plant growth progress in lab scale level revealed a significant growth of the Black eye beans plant growth after treatment of the hybrid chitosan-calcium oxide nanoparticle (8cm, 10.7cm) in comparison with untreated (6cm) after 7 days of experimental stage. The observation of the study revealed that hybrid chitosan-calcium oxide nanoparticles can be used to enhance the growth of Black eye bean plant and inferred that these nanoparticles may be used for other plants also.